Equilibrium selection in sequential games with imperfect information - Jon X. Eguia; Aniol Llorente-Saguer; Rebecca Morton; Antonio Nicolò (Max Planck Institute for Research on Collective Goods, 2014)
Games with imperfect information often feature multiple equilibria, which depend on beliefs off the equilibrium path. Standard selection criteria such as passive beliefs, symmetric beliefs or wary beliefs rest on ad hoc restrictions on beliefs. We propose a new selection criterion that imposes no restrictions on beliefs: we select the action profile that is supported in equilibrium by the largest set of beliefs. We conduct experiments to test the predictive power of the existing and our novel selection criteria in two applications: a game of vertical multi-lateral contracting, and a game of electoral competition. We find that our selection criterion outperforms the other selection criteria.
Keywords: H41; C72; D86; D72; 330; imperfect information; equilibrium selection; passive beliefs; symmetric beliefs; vertical contracting; multiple equilibria